2021
DOI: 10.1108/arj-05-2021-0144
|View full text |Cite
|
Sign up to set email alerts
|

Understanding inhibitors to XBRL adoption: an empirical investigation

Abstract: Purpose This study aims to investigate the awareness of extensible business reporting language (XBRL) and the perception of chartered accountants of India concerning the inhibitors of XBRL adoption, namely, environmental, organizational and innovation factors developed by Troshani and Rao (2007) from Rogers’ innovation diffusion theory. In addition, the analysis also investigated the relationship between the perception of issues regarding XBRL adoption and individual characteristics (training, age, gender and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The authors found that firm size and industry sector did not significantly affect the adoption of epayment systems, which also found no significant relationship between microentrepreneurs use of e-payment and position or business location. These findings are consistent with the study by Singh and Dwivedi (2021) examines the factors influencing the adoption of e-payment systems in micro-enterprises. One of the findings is that the business profile variables of micro-enterprises, including business type, size, and years in operation, do not significantly affect the adoption of e-payment systems.…”
Section: Resultssupporting
confidence: 92%
“…The authors found that firm size and industry sector did not significantly affect the adoption of epayment systems, which also found no significant relationship between microentrepreneurs use of e-payment and position or business location. These findings are consistent with the study by Singh and Dwivedi (2021) examines the factors influencing the adoption of e-payment systems in micro-enterprises. One of the findings is that the business profile variables of micro-enterprises, including business type, size, and years in operation, do not significantly affect the adoption of e-payment systems.…”
Section: Resultssupporting
confidence: 92%
“…According to Graeml (2003) e Weill e Ross (2020), the benefits derived from the adoption of a technology are a function of the actual consequence of its adoption. Thus, the more a technology is adopted, the more it is used, the more can be learned about it (Singh & Singh, 2022), and the more it will be developed and improved, since it will be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used TAM or DIT to explain XBRL (Hentati et al , 2021; Singh and Singh, 2022; Mousa and Pinsker, 2020), which can be used to study technology adoption and innovation in the context of MBRS adoption. TAM and DIT elements can be combined to create a more convincing model (Chen et al , 2002).…”
Section: Theoretical Model and Hypothesesmentioning
confidence: 99%
“…Previous XBRL studies have been conducted to understand the challenges to adoption (Ansary et al , 2020). However, the scope of these studies is less studied in the post-mandate XBRL context (Singh and Singh, 2022), particularly MBRS. Studies on the MBRS have been conducted in developed countries (Alkhatib et al , 2019; Shan and Troshani, 2021; Mousa and Pinsker, 2020; De Martinis et al , 2020) but relatively few in emerging countries such as Malaysia.…”
Section: Introductionmentioning
confidence: 99%